Association of inflammatory markers with hearing loss in young adults. (2nd January 2023) - Shapira, Udi; Ben Assayag, Hadas; Ungar, Omer J.; Handzel, Ophir; Abu Eta, Rani; Rogowski, Ori; Zeltser, David; Berliner, Shlomo; Shenhar‐Tsarfaty, Shani; Oron, Yahav
Abstract: Objectives: To assess the correlation between inflammatory markers (IM) and hearing loss (HL) in a large cohort of apparently healthy individuals. Design: A cross sectional study. Setting: Tel‐Aviv Medical Center (a tertiary referral center) Inflammatory Survey Participants Individuals who attended the Tel‐Aviv Medical Center Inflammatory Survey (TAMCIS) for a routine annual health check. Results: Out of 2, 500 individuals included in the final study cohort, 1, 170 (47.3%) had some hearing impairment. Those with a hearing loss in 1 or both ears had significantly higher levels of neutrophils, lymphocytes, neutrophil‐to‐lymphocyte ratio, monocyte‐to‐lymphocyte ratio, and red blood cell counts. There was a difference between low‐ and high‐ frequencies losses associated with the inflammatory status. Conclusions: IM levels were associated with the presence of a HL, supporting a link between inflammatory changes and hearing loss.